Turn-end Estimation in Conversational Turn-taking: The Roles of Context and Prosody. Issue 10 (26th November 2021) - Bögels, Sara; Torreira, Francisco
ABSTRACT: This study investigated the role of contextual and prosodic information in turn-end estimation by means of a button-press task. We presented participants with turns extracted from a corpus of telephone calls visually (i.e., in transcribed form, word-by-word) and auditorily, and asked them to anticipate turn ends by pressing a button. The availability of the previous conversational context was generally helpful for turn-end estimation in short turns only, and more clearly so in the visual task than in the auditory task. To investigate the role of prosody, we examined whether participants in the auditory task pressed the button close to turn-medial points likely to constitute turn ends based on lexico-syntactic information alone. We observed that the vast majority of such button presses occurred in the presence of an intonational boundary rather than in its absence. These results are consistent with the view that prosodic cues in the proximity of turn ends play a relevant role in turn-end estimation.